Sale & Purchase Agreement through Internet: The Legal Certainty for the E-Commerce Practices in Indonesia - Firqotun Naziah (Universitas Negeri Semarang, 2022)
E-commerce is a form of trade which has its own characteristics that are cross-border trade, not to meet the seller and buyer, use media internet. The birth of Law No. 11 of 2008 is about Information and Electronic Transactions (UU ITE) seems to be the solution to provide protection for consumers. In the ITE Law has set the terms validity of e-commerce transactions, establishing the rights and obligations, prohibited acts, responsibility, legal protection, remedies, and dispute resolution in e-commerce transactions. The purpose of this study is to analyze the legal certainty aspect on the buying and selling agreement on electronic commerce cases in Indonesia.